Age at first calving and lifetime performance of Hariana cattle at organized farms - SHETKAR, MAHANTESH; KUMAR, VIJAY; SINGH, S P; SINGH, YAJUVENDRA; KUMAR, MUNEENDRA; NATH, SHASHANK (The Indian Journal of Animal Sciences, 2022)
The present investigation was undertaken to access age at first calving, actual lifetime milk yield per day of productive life, actual lifetime milk yield per day of herd life and actual lifetime milk yield per day of total life. The non-genetic factors such as period of birth, season of birth, AFC age group and farms on these traits were studied by least-squares analysis and the means were compared using Duncan's multiple range test. The least-squares means for age at first calving, actual lifetime milk yield per day of productive life, actual lifetime milk yield per day of herd life and actual lifetime milk yield per day of total life were estimated as 1668.3±16.6 days, 1.878±0.04 litres/day, 1.735±0.05 litres/day and 1.029±0.03 litres/day respectively. Farm and period of birth had significant effect on age at first calving, actual lifetime milk yield per day of herd life and actual lifetime milk yield per day of total life. In actual life time milk yield per day of productive life, period of birth had significant effect. AFC class had significant effect on actual lifetime milk yield per day of total life.